RANCANG BANGUN AKUAPONIK BERBASIS INTERNET OF THINGS - I Made Kris Widiantara; Linawati Linawati; Dewa Made Wiharta (Program Studi Teknik Elektro UNUD, 2021)
Currently technology is growing so that many tools are created, especially reforms inagriculture. Aquaponics is a combination of hydroponic and aquaculture techniques intoaquaponics techniques. This aquaponics technique only uses water as a growing medium.Cultivating aquaponics does not require a large area of land, it can be done in the yard of ahouse that does not have a large area. Currently aquaponics techniques have developed,especially in modern agriculture because this aquaponics technique will use an Internet ofThings (IoT) based system. Internet of Things (IoT) is a concept in which the virtual world of information technology blends with real objects in the real world. In other words, the Internetof Things (IoT) is a concept which aims to expand the benefits of continuously connectedinternet connectivity. This system is built using the Node Mcu Esp8266 microcontroller as thecontrol center and uses the Raspberry Pi 3 type B mini PC as visual notification and is equippedwith a pH sensor 4502C, DS18B20 temperature sensor, Servo Motor, SRF05 sensor. A plantcommonly used in aquaponics is pakcoy, which is one of the most widespread vegetables inAsia. While the fish used in aquaponics techniques are freshwater fish, one of which is parrotfish. In testing the pH sensor is carried out with 3 conditions, namely when the pH is normal,acidic and alkaline on the sensor test detects normal pH, acid and alkaline approaching theresults of the pH meter comparison tool, then the water level test is carried out with 2 conditions,namely when the water is normal and reduced by using a ruler comparison tool, where thesensor has a little detecting error, on testing the water temperature sensor using a thermometercomparator has an error detecting the state of the aquaponic water temperature. When testingthe chat feature is done by typing / getdata, the application will send a chat with sub watertemperature, water level, water pH, then testing the camera feature is done by typing /getpHoto, the application will send a picture of the condition of the aquaponics.